The Relationship Between Spirituality Dimensions and Death Anxiety among Iranian Veterans: Partial Least Squares Structural Equation Modeling Approach - Saeed Pahlevan Sharif (Journal of religion and health, 2021)
The purpose of the present study was to examine the relationship among spiritual intelligence, spiritual well-being and death anxiety among Iranian veterans. In this predictive correlational study, 211 veterans completed King and DeCicco’s Spiritual Intelligence Scale, Paloutzian and Ellison’s Spiritual Well-being Scale and Templer’s Death Anxiety Scale-Extended. After confirming the reliability of the constructs using intra-class correlation coefficient, partial least squares structural equation modeling method was utilized to assess the impact of spiritual well-being and spiritual intelligence on death anxiety. This study found a significant positive relationship between spiritual intelligence and death anxiety after controlling for the effects of age, education level and disability. However, there was a significant negative relationship between spiritual well-being and death anxiety among Iranian veterans. Negative relationships were found between spiritual well-being and death anxiety among Iranian veterans. However, spiritual intelligence had a positive impact on death anxiety.